Colonial Hospital, Port of Spain, Trinidad - (:unkn) unknown (My University, 2009)
Photo of the Colonial Hospital located in Port of Spain, Trinidad. Photo provides a side view of the building with palm trees, car park with vehicles and a view of the Northern Range in the background. There is also a male person exiting the building.
Colour: Black and White; Style: Landscape : Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Hospitals--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain